MEDIASI JOB INNOVATION DALAM PENINGKATAN JOB PERFORMANCE PADA MASA PANDEMI COVID 19 - Galih Fajar Muttaqin; Asih Machfodzhoh; Nabilla Audrey Frishilla (Jurnal Akademi Akuntansi, 2021)
This study aims to examine the effect of Empathetic Leadership on Job Performance with Job Innovation as an Intervening variable. This research is a type of quantitative research, data is collected using primary data and questionnaires to obtain information from respondents, namely middle managers who work in manufacturing companies in the provinces of DKI Jakarta, Banten and Answerarat. The analytical method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) Path Modeling with the SmartPLS 2.0 analysis tool. The result of this research is that Empathetic leadership has an effect on Job Innovation and Job Performance. Empathetic leadership affects Job Performance through Job Innovation.